Priorities for eliminating legal barriers in the energy transformation of heating in the assessment of the heating industry and representatives of the regulator - Niestępska, Małgorzata (Instal, 2025)
In February 2025, representatives of the heating industry and URE met in Lublin at the 14th District Heating Market Conference organized by the Polish Heating Chamber of Commerce and jointly participated in workshops entitled "Priorities for eliminating legal barriers in the energy transformation of heating". The aim of the workshops was to determine the most urgent, in the opinion of the industry, changes in the applicable law creating barriers to the implementation of investments in the transformation of heating systems and having a negative impact on the economic situation of the industry. In the transformation, the effects that guarantee the future of the industry operating on the market of substitution competition are important, i.e. an acceptable, long-term stable heat price, security measured by the reliability of supplies, which is inextricably linked to the economic security of enterprises. The aim of the workshops was to address the question: Do the directions set by EU law and trends indicated in the media, i.e. maximization of energy generation from RES, climate neutrality and electrification provide the industry with these effects? During the workshops heating representatives discussed and assessed these important issues, being aware of the uncertainty and risks of contemporary functioning and the importance of decisions currently being made about the direction and effects of investments. As part of the three workshop parts, research was conducted with the presense of 39 participants representing the by heating market using research tools such as a survey and brainstorming. As part of the survey aimed at identifying legal barriers, two basic aspects of heating operations were analyzed: economic and technological. The research results reveal a vision of the future of district heating in the light of a series of crises in recent years, which have shaken energy markets and forced the need to revise policies and take a new look at the issue of energy security. The results of the conducted research constitute material that organizes the priorities for eliminating legal barriers and may constitute the assumptions of the concept of improving the economic security of enterprises. A critical look at the realities of transformation in the technological and economic aspect and initiating the elimination of transformation barriers in acceptable and considered realistic directions, complementing each other, should allow for the effect of “antifragility” of the industry in the face of geopolitical crises and climate change.